Potensi Aloe vera sebagai Bahan Disinfeksi Kon Gutaperca sebelum Pengisian Saluran Akar - As Syifa Faradita; Rina Permatasari (Faculty of Dentistry Universitas Andalas, 2023)
Background: Obturation of the root canal aims to close access from the coronal and from the apical into the root canal. Currently the most widely used root canal filling material is guttapercha, due to its plastic properties, easy to manipulate, and easy to remove if necessary. Before use, guttapercha should be disinfected first to avoid re-infection of the root canal. One of the herbal plants that can be used as a guttaperca disinfectant is the Aloe vera plant because it contains phytochemical compounds that are antibacterial. Objective: To explain the potency of the herbal plant Aloe vera as a guttaperca disinfectant before root canal filling. Method: Collecting references in the form of research reports and literature studies as well as textbooks containing theories related to writing titles accessed through the Google Scholar, Research Gate, and NCBI databases published from 2012–2021. Conclusion: Aloe vera has the potential as an alternative material for disinfecting gutta percha because it has a fairly good antibacterial effect with very minimal side effects, so that Aloe vera can be a promising disinfectant in the future.